Structural variety in ytterbium dicarboxylate frameworks and in situ study diffraction of their solvothermal crystallisation - Breeze, M; Chamberlain, T; Clarkson, G; de Camargo, R; Wu, Y; de Lima, J; Millange, F; Serra, O; O'Hare, D; Walton, R (Royal Society of Chemistry, 2017)
The ytterbium 1,4-benzenedicarboxylate (BDC) framework [Yb2(BDC)3(DMF)2]·H2O (1) crystallises from a N,N-dimethylformamide (DMF)-rich solution at 80–120 °C. (1) is constructed from infinite chains of dicarboxylate-bridged seven-coordinate Yb atoms, cross-linked in two directions by BDC to yield diamond-shaped channels (sra topology) lined by coordinated DMF molecules and occluded water. Increasing the water content in the synthesis solution yields a material with more crystal water Yb2(BDC)3(DMF)2(H2O)2 (2), in which the Yb centres are eight-coordinate and form dimers bridged by BDC to give two interpenetrating networks of pcu (α-Po) topology. Upon extended reaction in this water-rich solvent mixture, an alternative phase is formed: an anhydrous mixed BDC-formate, Yb(BDC)(HCO2), (3), which has a pillared, layered structure, with formate produced by hydrolysis of the DMF. An isoreticular version of (2) can also be formed under similar conditions using 2,6-naphthalene-dicarboxylate (NDC) as linker: [Yb2(NDC)3(H2O)4]·2DMF (4). Despite their different structures, (1) and (2) are calcined to a common porous, desolvated phase Yb2(BDC)3 at 300 °C. Using high energy X-rays at Diamond Light Source we are able to penetrate the solvothermal reaction vessels and to follow the formation of (1) and (2) in real time. This allows accurate crystallisation curves to be obtained from which qualitative kinetic information is extracted. Importantly, the high angular resolution of the in situ powder XRD patterns allows refinement of crystal structure: this permits the temporal evolution of unit cell parameters to be followed, which are ascribed to changes in coordinated solvent composition within the materials during their formation, while analysis of phase fraction allows kinetic parameters to be quantified using the nucleation-growth model of Gualtieri.